Women’s Societal Convention and Individual Independence in Jane Austen’s Sense and Sensibility, Pride and Prejudice, and Emma - Alam, Ahmad Mahbub ul; Nisa, Noshin (Feni University Journal, 2026)
This study examines the portrayal of feminism in the 19th-century novels of the English novelist Jane Austen, specifically in her works Sense and Sensibility, Pride and Prejudice, and Emma. The paper analyses how Austen builds emotionally strong, self-aware, and intelligent female protagonists who navigate patriarchal limitations and claim their power within these boundaries with resilience, introspection, and a mindset of strength and tolerance. Through close reading, this study demonstrates how Austen’s protagonists subtly rebel against adversity with their impeccable social intelligence, exhibiting just the right amount of defiance to obtain what they are entitled to, while respecting social and familial dynamics and maintaining their grounds. Austen’s protagonists reflect the reality of her time, in which women were unable to escape societal restrictions. Still, they also reflect a woman’s strength in surviving on her own terms, embracing opportunities amid her limitations. The present study also discusses the natural and gradual development of characters like Elinor, Marianne, Elizabeth, and Emma, which reflects Austen’s internalized feminist commentary on her society, where emotional intelligence serves as a tool of survival. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (237-252)